PENGARUH KUALITAS PELAYANAN PADA KEPUTUSAN PEMBELIAN PADA PT. PRIMA FAJAR MANDIRI PADANG PANJANG - Ary Kurniawan (JURNAL PUNDI, 2021)
This study aims to find out the influence of service quality, namely: tangible (physical evidence), empathy (empathy), reliability (reliability), responsiveness (response) and assurance (assurance) on consumer decisions. Pt. Prima Fajar Mandiri Padang Panjang. Popuulasi in this study as many as 77 respondents, sampling was done using the total sampling method. Data collection techniques are done by questionnaire. Data analysis is conducted with multiple regression analyst techniques. The results showed that tangilble (physical evidence), empathy (empathy), reliability (reliability), responsiveness (response) and assurance (guarantee) had a positive and significant effect on purchasing decisions.Keywords: quality of service, purchasing decisions.